2021
DOI: 10.1002/adem.202001129
|View full text |Cite
|
Sign up to set email alerts
|

General Strategy for Fabrication of Ordered One Dimensional Inorganic Structures by Electrospinning: Structural Evolution From Belt to Solid via Hollow Tubes

Abstract: Increasing profound interest in methods to fabricate complex hollow superstructures in terms of shell architecture is highly desirable for the realization of various functionalities. Recent efforts in this direction have strongly suggested that unlike other hollow structures, tubular structures do not have well-developed nanostructure library, and establishing a general method remains a significant challenge. Hollowstructured metal oxides have emerged as one of the most propitious functional materials by virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…As a “brother” technology of electrospraying, electrospinning uses electrostatic field forces to fabricate continuous micro-/nanofibers. In recent years, coaxial electrospinning, an “improved version” of traditional single-fluid electrospinning, has been developed and widely used in the preparation of functional materials. The encapsulation efficiency and release characteristics of the drug will be improved when they attach to the surface of the carrier or are encapsulated inside. Inspired by this concept, a series of drug-sustained release strategies have been realized by electrospinning medicine nanofibers …”
Section: Introductionmentioning
confidence: 99%
“…As a “brother” technology of electrospraying, electrospinning uses electrostatic field forces to fabricate continuous micro-/nanofibers. In recent years, coaxial electrospinning, an “improved version” of traditional single-fluid electrospinning, has been developed and widely used in the preparation of functional materials. The encapsulation efficiency and release characteristics of the drug will be improved when they attach to the surface of the carrier or are encapsulated inside. Inspired by this concept, a series of drug-sustained release strategies have been realized by electrospinning medicine nanofibers …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the composition and structure of electrospun fiber can improve and change their properties and applications. The common secondary structure of the electrospinning fiber is porous [23][24][25][26], hollow [27][28][29][30], groove [22,31,32], belt-like [33], etc. The coarse surface of grooved fibers is conducive to cell adhesion, and the orientation of groove fibers can induce axon growth well, so groove fibers can be used for tissue engineering [34].…”
Section: Introductionmentioning
confidence: 99%